МОДЕЛИРОВАНИЕ И ОЦЕНКА СИСТЕМООБРАЗУЮЩИХ СВЯЗЕЙ РЕЛЬЕФА В БАССЕЙНЕ МАЛОЙ РЕКИ - Куценко Н.В. (My University, 2005)
The relationship between riverbed profiles and the structural components of small river basins has been established. The author has developed a procedure for estimation the role of slopes, ravines, and gullies in riverbed formation and has applied it to a specific river. The procedure was used for optimization the meliorative measures at small river basins.
Keywords: 551.4.01.013